Clinical audit of a sports psychiatry clinic in Malaysia - Yau, Eugene Koh Boon; Abdul Rauf, Anis Naazira; Rozley, Yasmin Hanani; Ping, Nicholas Pang Tze; Marhaban, Mohammad Hamiruce (Hogrefe Publishing, 2025)
Sports psychiatry is a young subspecialty of psychiatry that has expanded in recent decades. However, information on mental health issues among athletes remained limited. Malaysia’s first sports psychiatry clinic (SPC) was established in 2021. Methods: A clinical audit of the SPC was conducted to provide insight into the referral patterns, demographic characteristics of athletes seeking help, and the types of diagnoses and treatments received. This audit was conducted between September 2021 and October 2024. Results: Twenty-seven athletes were identified, with a mean age of twenty-one and a majority of female gender. The athletes came from various individual and team sports, had sports representation from school to national level and were commonly referred from a sports institution. Diagnoses received are primarily anxiety-related disorders. Notable non-DSM-5 diagnoses included athlete burnout, migraine, and post-concussion syndrome. The most common treatment modalities are either medication and psychotherapy or medication only. Conclusion: This audit highlights the low uptake of mental health services amongst athletes, the common diagnoses that present to SPC and the need for further development in this area.